Nilai-nilai Pendidikan Karakter dalam Al-Qur’an Surat Al-Isra’ - Fauzi, Muhammad Fauzi (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This research aims to reveal the values of moral education contained in Surah Al-Isra'. The questions asked in this research are: What are the values of Moral Education contained in Surah Al-Isra'? The method used in this research is qualitative research, by means of descriptions in the form of words and language in a special natural context and by utilizing various scientific methods. The findings of this research are: The Koran is a source of knowledge and education, especially in moral education, there are many norms that must be implemented in this life. In Surah al-Isra' there is a number of moral education, including: instilling the values of Birul Walidaini, advice on giving rights to relatives, prohibition on being wasteful (wasteful), prohibition on being stingy (bakhil) and prohibition on being arrogant. Of course, if these recommendations and prohibitions are violated, they will receive sanctions both socially and in the afterlife. In the world of Islamic education, there should be an emphasis on the field of moral studies related to Surah al-Isra'.